Réponses

  • Utilisateur Brainly
2013-06-22T12:26:46+02:00

-3x - 2x (7-4x) = 2x

donc -3x-14x+8x²=2x

donc 8x²-19x=0

donc x(8x-19)=0

donc x=0 ou x=19/8

-x -x -x - x/5 = x

donc -16/5x=x

donc x=0

x(x)²/4x   -  2x+1 = 0

donc pour x non nul

x²/4-2x+1=0

donc x²-8x+4=0

donc x=(8-√48)/2 ou x=(8+√48)/2
donc x=4-2√3 ou x=4+2√3


(x/2 - 2)² - x = 0

donc x²/4-2x+4-x=0

donc x²-12x+16=0

donc x=(12-√80)/2 ou x=(12-√80)/2

donc x=6-√20 ou x=6+√20

2013-06-22T12:30:14+02:00

-3x - 2x (7-4x) = 2x

⇒ -3x - 14x + 4x² = 2x

⇒ -17x + 4x² = 2x

⇒ 4x² = 17x

⇒ 4x = 17

⇒ x = 17/4

 

 

-x -x -x - x/5 = x

⇒ -3x -x/5 = x

⇒ -16x/5 = x

⇒ -x -16x/5 = 0

⇒ -21x/5 = 0

⇒ x = 0

 

 

x × x²/4x - 2x+1 = 0

⇒ x × x/4 -2x + 1 = 0

⇒ x²/4 -2x + 1 = 0

⇒ x² -8x + 4 = 0

⇒ (x - 2)² = 0

or (x - 2)² = (x - 2) (x - 2) qui est nul si l'un des facteurs est nul, soit si x - 2 = 0

⇒ x = 2

 

 

(x/2 - 2)² - x = 0